2008
DOI: 10.1037/a0012639
|View full text |Cite
|
Sign up to set email alerts
|

Work strain, health, and absenteeism: A meta-analysis.

Abstract: Work strain has been argued to be a significant cause of absenteeism in the popular and academic press. However, definitive evidence for associations between absenteeism and strain is currently lacking. A theory focused meta-analysis of 275 effects from 153 studies revealed positive but small associations between absenteeism and work strain, psychological illness, and physical illness. Structural equation modeling results suggested that the strain-absence connection may be mediated by psychological and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
235
1
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 308 publications
(264 citation statements)
references
References 260 publications
(155 reference statements)
10
235
1
14
Order By: Relevance
“…In addition, 4 studies allowed us to calculate the diagnostic odds ratio (Glas, Lijmer, Prins, Bonsel, & Bossuyt, 2003), an overall measure of diagnostic accuracy expressing the strength of association between the questionnaire measuring absenteeism and actual absence behavior. These studies, which also speak to convergent validity, were analyzed separately, as in Darr and Johns (2008).…”
Section: Methods the Meta-analytic Databasesmentioning
confidence: 99%
“…In addition, 4 studies allowed us to calculate the diagnostic odds ratio (Glas, Lijmer, Prins, Bonsel, & Bossuyt, 2003), an overall measure of diagnostic accuracy expressing the strength of association between the questionnaire measuring absenteeism and actual absence behavior. These studies, which also speak to convergent validity, were analyzed separately, as in Darr and Johns (2008).…”
Section: Methods the Meta-analytic Databasesmentioning
confidence: 99%
“…Stress is worthy of particular attention. A metaanalysis by Darr and Johns (2008) reveals a rather modest negative correlation between work stress (specifically, strain) and absence. This small association might be due to the fact that stress is not seen as an especially legitimate reason to be absent (Johns & Xie, 1998), a potential recipe for presenteeism.…”
Section: Toward a Theory Of Presenteeismmentioning
confidence: 99%
“…Specifically, Duijts et al [39] reported that the presence of psychological symptoms was associated with increased risk of sick leave of 3 days or less (adjusted OR = 1.27) and of more than 3 days (adjusted OR = 1.97). Darr and Johns [53] discussed a relationship between psychological illness and increased risk of absenteeism. O'Neil et al [37] reported that depression resulted in decreased work resumptions following myocardial infarction.…”
Section: Psychological Symptomsmentioning
confidence: 99%